2021
DOI: 10.3390/polym13020201
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Self-Healing Epoxies in Polymer Matrix Composites (PMCs) for Aerospace Applications

Abstract: This article reviews some of the intrinsic self-healing epoxy materials that have been investigated throughout the course of the last twenty years. Emphasis is placed on those formulations suitable for the design of high-performance composites to be employed in the aerospace field. A brief introduction is given on the advantages of intrinsic self-healing polymers over extrinsic counterparts and of epoxies over other thermosetting systems. After a general description of the testing procedures adopted for the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 137 publications
(205 reference statements)
1
64
0
Order By: Relevance
“…Hence, although the healing efficiency equation has been extensively used for self-healing studies, a need for standardized methods for self-healing measurements still exists. In addition, when results of healing efficiencies obtained through different methods were compared it was found that healing protocols can be highly inaccurate and therefore not recommended [10,11].…”
Section: Property Value Healed Healing Efficiencymentioning
confidence: 99%
“…Hence, although the healing efficiency equation has been extensively used for self-healing studies, a need for standardized methods for self-healing measurements still exists. In addition, when results of healing efficiencies obtained through different methods were compared it was found that healing protocols can be highly inaccurate and therefore not recommended [10,11].…”
Section: Property Value Healed Healing Efficiencymentioning
confidence: 99%
“…Polymers has been widely used in aerospace, automation, civil engineering, marine engineering and other fields [ 1 , 2 , 3 , 4 , 5 ]. According to the composition and type, it mainly includes the thermosetting resin (such as epoxy) with the three-dimensional network crosslinking structure and thermoplastic resin with the linear molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49][50] From a commercial perspective, epoxy-based polymers are relevant to the fields of aerospace, transportation, civil engineering, home and office goods, and coatings. [51][52][53][54] They generally possess high T g , strength, and toughness, while maintaining excellent moisture, chemical and corrosion resistance. Furthermore, their final properties can be readily tuned thanks to a wide range of commercially available monomers.…”
Section: Introductionmentioning
confidence: 99%